Are small-sized mechanical valves adequate for patients with small aortic roots?. (November 2022) - Pandey, Pratik; Saha, Apu; Jha, Neeraj Kumar; Rao, Yashaskar Manjunatha; Das, Debasis; Das, Mrinalendu; Chatterjee, Debika; Narayan, Pradeep
Aim: Concerns have been raised over patient outcomes following implantation of small aortic valves (size: 19 and 17 mm). However, in patients with a smaller body surface area, these valves may be adequate. The aim of th study was to assess the hemodynamic and functional performance of these valves and their impact on clinical outcomes in patients with a small aortic root. Material and methods: This was a prospective observational study that included all consecutive patients undergoing aortic valve replacement (AVR) with a small-sized aortic valve over a 3-year period. Patients were followed up at 1 week, 6 weeks, and 1 year. Functional and clinical evaluation along with echocardiography was carried out for hemodynamic assessment. In-hospital mortality and hemodynamic outcomes at 1-year follow-up were recorded. Results: Isolated AVR with a size 17 mm valve was carried out in 15 (25%) and with a 19 mm valve in 45 (75%) patients. The mean annular size was 19.12 ± 2.03 mm. The mean indexed effective orifice area was 1.08 ± 0.16 cm 2 /m 2 . Satisfactory decrease in peak and mean trans-prosthetic gradient were evident (peak gradient preoperatively was 92.15 ± 26.2 mmHg, and 25.68 ± 12.28 mmHg at 1 year, mean gradient was 55.31 ± 17.41 mmHg preoperatively and 13.71 ± 7.39 mmHg at 1 year). The functional status of patients also showed significant improvement post AVR. Left ventricular ejection fraction pre-operatively was 59.67% ± 10.38% and 59.57% ± 7.98% at 1-week, 59.15% ± 8.17% at 6 weeks, and 59.59% ± 7.48% at 1 year. Conclusion: When confronted with a small aortic root, AVR with a small-sized prosthesis provides a satisfactory hemodynamic and functional outcome. In patients with small body surface area, implantation of a small-sized valve is a viable option.